Análise e sugestões terapêuticas das manifestações patológicas de infiltração de um edifício com mais de 20 anos: estudo de caso - Castro, Maicon Dioni de (2014)
This work presents the pathological manifestations of existing infiltration in a building with more than 20 years and suggests possible therapies for identified cases. Moreover, mentions a set of regulatory rules setting guidelines for the proper functioning of the building and governing the relations between supplier and consumer. The study is grounded in the literature of the area and does not address details regarding costs. Moreover, exposes the different origins of diseases, ranking design flaw, incorrect specification of materials or poor quality of execution failure, incorrect or nonexistent maintenance and misuse materials.